2015
DOI: 10.5194/acp-15-3909-2015
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of atmospheric OH, O<sub>3</sub> and NO<sub>3</sub> reactivities within and above the boreal forest

Abstract: Abstract. Using the 1-D atmospheric chemistry transport model SOSAA, we have investigated the atmospheric reactivity of a boreal forest ecosystem during the HUMPPA-COPEC-10 campaign (summer 2010, at SMEAR II in southern Finland). For the very first time, we present vertically resolved model simulations of the NO 3 and O 3 reactivity (R) together with the modelled and measured reactivity of OH. We find that OH is the most reactive oxidant (R ∼ 3 s −1 ) followed by NO 3 (R ∼ 0.07 s −1 ) and O 3 (R ∼ 2 × 10 −5 s … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 83 publications
1
77
1
Order By: Relevance
“…SOSAA has already been applied and verified in several studies (e.g. Kurtén et al, 2011;Mogensen et al, 2011Mogensen et al, , 2015Boy et al, 2013;Bäck et al, 2012;Smolander et al, 2014;Zhou et al, 2015).…”
Section: Classification Of Time Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…SOSAA has already been applied and verified in several studies (e.g. Kurtén et al, 2011;Mogensen et al, 2011Mogensen et al, , 2015Boy et al, 2013;Bäck et al, 2012;Smolander et al, 2014;Zhou et al, 2015).…”
Section: Classification Of Time Periodmentioning
confidence: 99%
“…The related chemical reactions of stabilised Criegee intermediates (sCIs) with updated reaction rates from Boy et al (2013) are also taken into account in current simulations. For more details about emissions and chemistry we refer to Mogensen et al (2015).…”
Section: Classification Of Time Periodmentioning
confidence: 99%
“…The strongest gradient modeled is again a few hundred meters lower than the sounding data. This tendency of SOSAA to slightly underestimate the height of the mixed layer has also been observed in studies made in Hyytiälä, Finland (Mogensen et al, 2015). At 22:00:00 LT, the nocturnal boundary layer has built up.…”
Section: Meteorologymentioning
confidence: 52%
“…After this time, the model results become higher than the observations, which should result from (1) missing sinks and (2) overestimated production. The missing sink terms have been studied previously at MEFO by Nakashima et al (2014). Based on measurements, Nakashima et al (2014) concluded a missing OH reactivity of 29.5 %, which may mainly be due to oxidized products of biogenic species.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation